Użądlenie rogówki przez pszczołę – opis przypadku - Gerkowicz, Marek; Matysik, Anna; Gruszecka-Gerkowicz, Renata (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Published reports on bee stings of the cornea are rare, especially when it occurs in the winter season. These injuries have the potential for causing serious ophthalmologic problems. The venom in the sting can produce toxic and immunologic reactions. The result is acute ocular inflammation, which is usually confined to the anterior segment of the eye. The aim of our work is to present 84-year-old man who was stung by a bee on the left cornea, while taking care of a swarm of bees. The main symptoms were pain, oedema of eyelids, conjunctival injection, keratitis and iritis. The sing was present in the cornea. After the removal of retained stinger and pharmacological treatment we observed the rapid improvement.